Numerical Study of the Effects of Topography and Urbanization on the Local Atmospheric Circulations over the Beijing-Tianjin-Hebei, China - Yucong Miao; Shuhua Liu; Yijia Zheng; Shu Wang; Bicheng Chen (Advances in Meteorology)
The effects of the topography and urbanization on the local atmospheric circulations over the Beijing-Tianjin-Hebei (BTH) region were studied by the weather research and forecasting (WRF) model, as well as the interactions among these local atmospheric circulations. It was found that, in the summer day time, the multiscale thermally induced local atmospheric circulations may exist and interact in the same time over the BTH region; the topography played a role in the strengthening of the sea breeze circulations; after sunset, the inland progress of sea breeze was slowed down by the opposite mountain breeze; when the land breeze circulation dominated the Bohai bay, the mountain breeze circulation can couple with the land breeze circulation to form a large circulation ranging from the coastline to the mountains. And the presence of cities cannot change the general state of the sea-land breeze (SLB) circulation and mountain-valley breeze (MVB) circulation but acted to modify these local circulations slightly. Meanwhile, the development of the urban heat island (UHI) circulation was also strongly influenced by the nearby SLB circulation and MVB circulation.